Salat Jumat Setelah Salat Hari Raya Id Saat Pandemi Covid-19 dalam Perspektif Hukum Islam - Asri; Sam, Zulfiah; Damayanti, Rezky (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2020)
This study aims to find out how the laws of Friday prayers after Eid prayer in an Islamic perspective and how the laws of Friday prayers after Eid prayers during the Covid-19 pandemic. The research method used is library research (library research), namely through literature review related to the above problems, with normative and historical approaches. The research results found are as follows; First, the law of Friday prayers after the Eid prayer is disputed by scholars in three views: First opinion: Friday prayers are compulsory for people who attend holiday prayers like Friday on any other day. Second opinion: Rukhá¹£ah is given to leave Friday prayers for Muslims who come from hamlets to the city to perform special prayers and Friday prayers. Third opinion: A person who has performed the Eid prayer, his obligation to perform Friday prayer is null and void, but it is appropriate for the priest to establish Friday prayers so that people who wish to attend them can attend. And for Muslims who have attended the holiday prayers, they are obliged to do the midday prayer on time if they do not do the Friday prayers. As for the law of implementing Friday prayers after the implementation of the Ied prayers in the midst of the Covid 19 pandema, the law of returning to the original law will still be mandatory for areas or zones that are still considered safe in carrying out Eid prayers in congregation